Re-Accessing International Capital Markets After Financial Crises : Some Empirical Evidence - Zanforlin, Luisa (IMF Working Papers; Working Paper ;, 2007)
The paper analyzes the factors that contribute to the re-access of countries that emerge from a severe financial crisis to the international capital markets. It conjectures that these factors depend on a sovereign's commitment and ability to repay its foreign debt, signaled by sound macroeconomic policies, and the global liquidity environment. Using panel data for 49 countries over a 24-year period, the analysis uses a simple probit approach to show that, indeed, a sustainable debt profile and a sound external position, accompanied by a favorable global liquidity environment, are key factors in affecting the likelihood a sovereign reaccesses international capital markets.